2018
DOI: 10.1002/humu.23553
|View full text |Cite
|
Sign up to set email alerts
|

Improved, ACMG-compliant, in silico prediction of pathogenicity for missense substitutions encoded by TP53 variants

Abstract: Clinical interpretation of germline missense variants represents a major challenge, including those in the TP53 Li-Fraumeni syndrome gene. Bioinformatic prediction is a key part of variant classification strategies. We aimed to optimize the performance of the Align-GVGD tool used for p53 missense variant prediction, and compare its performance to other bioinformatic tools (SIFT, PolyPhen-2) and ensemble methods (REVEL, BayesDel). Reference sets of assumed pathogenic and assumed benign variants were defined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 20 publications
3
29
0
Order By: Relevance
“…(Spurdle et al, 2008;Spurdle et al, 2012;Thompson et al, 2014), and here we have developed the first quantitative model for TP53 variant classification. We estimated probability of pathogenicity using two bioinformatic tools previously selected as the best-performing tools for TP53 (Fortuno, James, Young, et al, 2018), but in this analysis, we converted the binary outputs to a continuous range of LRs for improved discrimination between variants. In addition, we used the relationship between somatic and germline counts (SGR), assisted by (Bouaoun et al, 2016), as a measure of the effect of genetic variation on TP53 gene function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Spurdle et al, 2008;Spurdle et al, 2012;Thompson et al, 2014), and here we have developed the first quantitative model for TP53 variant classification. We estimated probability of pathogenicity using two bioinformatic tools previously selected as the best-performing tools for TP53 (Fortuno, James, Young, et al, 2018), but in this analysis, we converted the binary outputs to a continuous range of LRs for improved discrimination between variants. In addition, we used the relationship between somatic and germline counts (SGR), assisted by (Bouaoun et al, 2016), as a measure of the effect of genetic variation on TP53 gene function.…”
Section: Discussionmentioning
confidence: 99%
“…Align‐GVGD (http://agvgd.hci.utah.edu) is a gene‐specific tool that considers physicochemical properties of amino acids and evolutionary conservation. The Grantham variation (GV) and deviation (GD) scores were calculated for each variant as previously described (Mathe et al, ), using an optimized protein multi‐sequence alignment (Fortuno, James, Young, et al, ). Overall, 76% of the assumed benign variants and 11% of assumed pathogenic variants fell into the lowest A‐GVGD category (C0), while 59% of assumed pathogenic variants and none of the assumed benign variants fell in the highest category (C65; Mathe et al, ; Tavtigian et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In silico analysis with IARC database including BaynesDel, PolyPhen2, REVEL and SIFT showed that 27 of these mutations might impair p53 transactivation activity. Mutations of arginine residue at codons R175H, R248Q, R273H and R282W might lead to gain of function enhancing oncogenesis and drug resistance (Table S2). Other genes co‐mutated with TP53 included BCOR (19%), RUNX1 (16%), NOTCH1 (16%), NRAS (11%), ASXL1 (11%) and BCORL1 (11%).…”
Section: Resultsmentioning
confidence: 99%
“…To do this, we excluded variants originally reported in the published studies as (likely) pathogenic if they were consistently reported in ClinVar as “(Likely) Benign”. In addition, variants found in ClinVar with conflicting classifications between “(Likely) Benign”/“Uncertain” were excluded if additional computational (Fortuno et al., ) and functional (Kato et al., ) evidence supported this exclusion. We also included in the meta‐analyses variants reported as uncertain by the original publications if they were consistently reported in ClinVar as “(Likely) Pathogenic”, or in ClinVar with conflicting classifications between “(Likely) Pathogenic”/“Uncertain” and if additional computational and functional evidence supported this inclusion.…”
Section: Methodsmentioning
confidence: 99%